PENGARUH MODEL PEMBELAJARAN CONCEPTUAL UNDERSTANDING PROCEDURES (CUPS) TERHADAP KEMAMPUAN CREATIVE PROBLEM SOLVING DAN METACOGNITIVE SKILL PESERTA DIDIK - Nurhidayati, Eka; Sumarmi, Sumarmi; Sahrina, Alfi; Wiwoho, Bagus Setiabudi; Wijayanto, Bayu (Jurnal Praksis dan Dedikasi Sosial (JPDS), 2024)
THE EFFECT OF THE CONCEPTUAL UNDERSTANDING PROCESS (CUP) LEARNING MODEL ON STUDENTS' CREATIVE PROBLEM SOLVING AND METACOGNITIVE SKILLS The current curriculum changes anticipate that students will possess problem-solving skills, metacognitive skills, and critical and creative thinking. One of the principal challenges currently facing educators is the lack of comprehension of the concepts being taught and the methods for solving problems. It is, therefore, necessary to adopt a learning approach that emphasises deeper conceptual understanding. The research was conducted at MAN Kota Mojokerto to determine the impact of the CUPs learning model on students' creative problem-solving abilities and metacognitive skills. This research employs a quasi-experimental pretest-posttest control group design. The sampling technique employed was purposive sampling, whereby class XI F7 was selected as the experimental class and class XI F8 was designated as the control class for comparison purposes. The research instruments comprised a description question for creative problem-solving ability, an inventory questionnaire for the measurement of metacognitive ability, and an observation sheet. The results of the MANOVA test indicate a significance value of 0.000, which is less than 0.05. Consequently, the null hypothesis (H0) is rejected and the alternative hypothesis (H1) is accepted. The results demonstrate that the implementation of the CUPs learning model has a notable impact on enhancing creative problem-solving abilities and metacognitive skills in students from class XI F7 of MAN Kota Mojokerto. The considerable effect can be substantiated by the improvement in test outcomes, indicating that the CUPs model effectively activates indicators on both dependent variables. Perubahan kurikulum saat ini mengharapkan kemampuan memecahkan masalah, keterampilan metakognitif, dan berpikir secara kritis serta kreatif dapat dimiliki oleh peserta didik. Salah satu hambatan utama sekarang ini adalah kurangnya pemahaman terhadap konsep yang diajarkan dan cara mengatasi permasalahan. Oleh karena itu, model CUPs dipilih sebab menekankan pemahaman konseptual yang lebih mendalam. Penelitian dilakukan di MAN Kota Mojokerto dengan tujuan untuk mengetahui pengaruh model pembelajaran CUPs terhadap kemampuan creative problem solving dan metacognitive skill peserta didik. Metode penelitian ini menggunakan quasi eksperimen pretest posttest control group design. Pengambilan sampel dilakukan dengan teknik purposive sampling, di mana kelas XI F7 dipilih sebagai kelas eksperimen, dan kelas XI F8 menjadi kelas kontrol untuk perbandingan. Instrumen penelitian melibatkan soal uraian untuk kemampuan pemecahan masalah secara kreatif, angket inventori untuk mengukur kemampuan metakognitif, dan lembar observasi. Hasil uji MANOVA menunjukkan nilai signifikansi 0,000 lebih kecil dari 0,05, sehingga hipotesis nol (H0) ditolak dan hipotesis alternatif (H1) diterima. Hal ini menunjukkan bahwa penerapan model pembelajaran CUPs secara bersamaan memberikan dampak yang signifikan terhadap peningkatan kemampuan creative problem solving dan keterampilan metakognitif pada peserta didik dari kelas XI F7 MAN Kota Mojokerto. Pengaruh signifikan tersebut dapat dibuktikan melalui peningkatan hasil pengujian, menunjukkan bahwa model CUPs berhasil mengaktifkan indikator-indikator pada kedua variabel dependen.